A morte e seus desdobramentos na obra "A morte de Ivan Ilitch", de Lev Tolstói: uma perspectiva psicanalítica - Mourão, Brunno Alvares Ataide (2024)
This work investigates death and its developments in the literary work The Death of Ivan Ilyich by Lev Tolstoy, from a Freudian psychoanalytic perspective, dialoguing with theories of literary criticism, such as Jean Bellemin-Noël's textanalysis and Roland Barthes' concept of the death of the author. It also integrates a historical-sociological overview based on the writings of Philippe Ariès, aiming to contextualize the cultural and social transformations that influenced the conception of death in the West and how they resonate in the work. From this panorama, the analysis seeks to understand how the protagonist, Ivan Ilyich, faced death, highlighting themes such as the loss of ideals, the denial of death (the belief in immortality in the unconscious), and the return to the infantile. Moreover, it explores, as its main focus, thedimensions of psychic suffering manifested in his self-recriminations through a diagnostic hypothesis that articulates the concepts of mania and melancholia. It also problematizes the use of psychoanalytic diagnosis in fictional characters, recognizing both the complexity and limitations of this approach. In this sense, the analysis not only opens discussions about the subjectivity of the character but also explores the possible traces of Tolstoy's life that permeate the work, challenging the notion of the "death of the author." Finally, the manic-melancholic hypothesis is presented as an interpretative possibility, without intending to establish a definitive diagnosis, thus allowing a more flexible reading that values the dialogue between the reader, the text, and the historical context